Influence of vitamin D supplementation on muscle strength and exercise capacity in South African schoolchildren: secondary outcomes from a randomised controlled trial (ViDiKids) - Cyrus Cooper; David A Jolliffe; Adrian R Martineau; Nicholas C Harvey; Keren Middelkoop; Jonathan C Y Tang; Robert J Wilkinson; Neil Walker; Lisa Micklesfield; Justine Stewart; Amy E Mendham; Stephanie Hemmings (BMJ Open Sport & Exercise Medicine)
Objective To determine whether vitamin D supplementation influences grip strength, explosive leg power, cardiorespiratory fitness and risk of exercise-induced bronchoconstriction (EIB) in South African schoolchildren.Methods Substudy (n=450) in Cape Town schoolchildren aged 8–11 years nested within a phase 3 randomised placebo-controlled trial (ViDiKids). The intervention was weekly oral doses of 10 000 IU vitamin D3 (n=228) or placebo (n=222) for 3 years. Outcome measures were serum 25-hydroxyvitamin D3 (25(OH)D3) concentrations, grip strength, standing long jump distance, peak oxygen uptake (VO2peak, determined using 20 m multistage shuttle run tests) and the proportion of children with EIB, measured at end-study.Results 64.7% of participants had serum 25(OH)D3concentrations <75 nmol/L at baseline. At 3-year follow-up, children randomised to vitamin D versus placebo had higher mean serum 25(OH)D3 concentrations (97.6 vs 58.8 nmol/L, respectively; adjusted mean difference 39.9 nmol/L, 95% CI 36.1 to 43.6). However, this was not associated with end-study differences in grip strength, standing long jump distance, VO2peak or risk of EIB.Conclusion A 3-year course of weekly oral supplementation with 10 000 IU vitamin D3 elevated serum 25(OH)D3 concentrations in South African schoolchildren but did not influence muscle strength, exercise capacity or risk of EIB.